Whose downtown is it anyways? The urban transformation of downtown Cairo between state and non-state actors - Awatta, Hajer (AUC Knowledge Fountain, 2015)
The purpose of this study is to examine how the influential state and non-state stakeholders interact, conflict and collectively shape the urban transformation of downtown Cairo. The stakeholder analysis revealed interesting positions and power levels of the influential stakeholders impacting urban transformation in downtown. It also illustrated alliances and dependencies between entities within the same stakeholder group and between state and non-state stakeholders. Collaborations between influential stakeholders in the private sector interested in establishing lobby groups to further their interests in downtown. Despite the commonalities between the interests of the state and private investors, the state prefers to maintain development monopoly and control over the area in its beautification-focused development efforts. Influential stakeholders who do not have particular interest in the development of downtown, such as legislative authorities and large financial institutions, whose power and influence can be tapped into and directed towards a more sustainable transformation of the area. The thesis findings revealed that the ingredients of gentrification are present in downtown however it is currently inhibited by legislative and other parameters. This brings up the question as to how the state is planning on regulating potential urban transformation in downtown Cairo in the current stakeholder power dynamics to minimize negative socioeconomic impacts. A clear comprehensive vision for the development of downtown can only be successfully implemented through the buy-in of all stakeholder groups.